Selection of indigenous isolates of entomopathogenic soil fungus Metarhizium anisopliae under laboratory conditions - Skalický, Aleš; Bohatá, Andrea; Šimková, Jana; Osborne, L.S.; Landa, Zdeněk (Springer Dordrecht, 2014)
Eight native isolates of the entomopathogenic fungus Metarhizium anisopliae (Metschnikoff) Sorokin were obtained by monitoring soils cultivated in a conventional manner. These isolates were compared in three areas: (a) conidial germination, (b) radial growth and sporulation and (c) ability of conidia to infect Tenebrio molitor larvae. All bioassays were carried out at constant temperatures of 10, 15, and 20 A degrees C. Conidia of individual isolates demonstrated differences in germination after a 24-h long incubation at all evaluated temperatures. At 20 A degrees C, the germination ranged from 67 to 100 % and at 15 A degrees C from 5.33 to 46.67 %. At 10 A degrees C, no germination was observed after 24 h; nevertheless, it was 8.67-44.67 % after 48 h. In terms of radial growth, the culture diameters and the associated production of spores of all isolates increased with increasing temperature. At 10 A degrees C, sporulation was observed in three isolates while all remaining cultures appeared sterile. Three weeks post-inoculation, conidia of all assessed isolates caused 100 % cumulative mortality of treated larvae of T. molitor at 15 and 20 A degrees C with the exception of isolate 110108 that induced 81.33 % mortality at 15 A degrees C. At 10 A degrees C, larval cumulative mortality ranged from 6.67 to 85.33 % depending on the isolate. Isolates 110108 and 110111 showed significantly slower outset and a much lower rate of infection at all temperatures compared to other tested isolates of M. anisopliae. The bioassays were carried out with the purpose to sort and select indigenous isolates of M. anisopliae useful as biocontrol agents in their original habitat.
Výběr nativních kmenů entomopatogenní půdní houby Metarhizium anisopliae v laboratorních podmínkách
Keywords: Conservation biological-control; Beauveria bassiana; growing media; radial growth; virulence; temperatures; rhizosphere; thermotolerance; sporulation; germination; Konzervativní biologická ochrana rostlin; Beauveria bassiana; živná média; radiální růst; virulence; teploty, rhizosféra; termotolerance; sporulace; klíčivost